2001
DOI: 10.1093/carcin/22.4.559
|View full text |Cite
|
Sign up to set email alerts
|

Se-Methylselenocysteine induces apoptosis through caspase activation in HL-60 cells

Abstract: Apoptosis, a programmed process of cell suicide, has been proposed as the most plausible mechanism for the chemopreventive activities of selenocompounds. In our study, we found that Se-methylselenocysteine (MSC) induced apoptosis through caspase activation in human promyelocytic leukemia (HL-60) cells. Measurements of cytotoxicity, DNA fragmentation and apoptotic morphology revealed that MSC was more efficient at inducing apoptosis than selenite, but was less toxic. Moreover, MSC increased both the apoptotic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(62 citation statements)
references
References 30 publications
4
57
0
Order By: Relevance
“…Recent studies have demonstrated that different selenium-containing compounds activate distinct cell death pathways in cancer cells. MSA-induced nucleosomal DNA fragmentation is accompanied by activation of various caspases, PARP cleavage and mitochondrial release of cytochrome c, whereas apoptotic DNA fragmentation induced by sodium selenite was observed in the absence of detectable caspase activity (Jiang et al, 2001;Kim et al, 2001). Caspases family members are also essential executors of apoptosis induced by Se-(Methyl)selenocysteine (Kim et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that different selenium-containing compounds activate distinct cell death pathways in cancer cells. MSA-induced nucleosomal DNA fragmentation is accompanied by activation of various caspases, PARP cleavage and mitochondrial release of cytochrome c, whereas apoptotic DNA fragmentation induced by sodium selenite was observed in the absence of detectable caspase activity (Jiang et al, 2001;Kim et al, 2001). Caspases family members are also essential executors of apoptosis induced by Se-(Methyl)selenocysteine (Kim et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…MSA-induced nucleosomal DNA fragmentation is accompanied by activation of various caspases, PARP cleavage and mitochondrial release of cytochrome c, whereas apoptotic DNA fragmentation induced by sodium selenite was observed in the absence of detectable caspase activity (Jiang et al, 2001;Kim et al, 2001). Caspases family members are also essential executors of apoptosis induced by Se-(Methyl)selenocysteine (Kim et al, 2001). In this study, we investigated the mechanism by which MSA augments TRAIL-induced cytotoxicity in prostate cancer cells and demonstrated that MSA modulates expression and activation of proteins involved in cell death signaling through both extrinsic and intrinsic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Selenium-induced apoptosis in vascular endothelial cells, leukemia HL-60 cells, prostate DU-145 cancer cells, and murine monocytic RAW264.7 cells activates caspase enzymes (53,(55)(56)(57). DNA fragmentation during the selenium-induced apoptotic process has been reported in various human cancer cell lines including HT29 and SW480 (colonic carcinoma), HepG2 (hepatic carcinoma), A172 and T98G (glioma), and HL-60 (leukemia), as well as the murine monocytic RAW264.7 cell line (57)(58)(59)(60)(61).…”
Section: Selenium-induced Apoptosismentioning
confidence: 99%
“…Methylselenocysteine is activated in the liver by h-lyase to its active metabolite methylselenol (24). Methylselenocysteine reportedly induces apoptosis through caspase-3 activation and cleavage of poly(ADPribose) polymerase (25,26), down-regulates inhibitors of apoptosis family proteins, which subsequently enhance apoptosis through Bax cleavage (25), regulates the cell cycle (block cells in S and G 1 phase; refs. 24,27), and reduces DNA synthesis and cell doubling rate (27 -29).…”
Section: Introductionmentioning
confidence: 99%